2001
DOI: 10.1038/35098125
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: A titanosilicate molecular sieve with adjustable pores for size-selective adsorption of molecules

Abstract: In the third sentence,``hyperglycaemia'' should have read``hypoglycaemia''. The corrected sentence is: "Here we show that mice carrying a targeted disruption of the cyclic AMP (cAMP) response element binding (CREB) protein gene, or overexpressing a dominant-negative CREB inhibitor, exhibit fasting hypoglycaemia and reduced expression of gluconeogenic enzymes." M

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Numerous studies have been reported using molecular‐sieving materials for gas separation. [ 16–20 ] Notably, graphene oxide‐based membranes stand out as excellent barrier films with both high permeability and also high selectivity. [ 10,13,21–23 ] As a noteworthy example, selectivity of over 3400 was reported for H 2 /CO 2 separation using graphene oxide‐based membranes with selective intrinsic defects.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been reported using molecular‐sieving materials for gas separation. [ 16–20 ] Notably, graphene oxide‐based membranes stand out as excellent barrier films with both high permeability and also high selectivity. [ 10,13,21–23 ] As a noteworthy example, selectivity of over 3400 was reported for H 2 /CO 2 separation using graphene oxide‐based membranes with selective intrinsic defects.…”
Section: Figurementioning
confidence: 99%
“…Since the [Ru(NH 3 ) 5 ] 2+ was demonstrated in 1965, [ 31 ] a number of other effective nitrogen adsorbents have been discovered. [ 8,17 ] Gas separators based on transition metals such as V (II), [ 32 ] Fe (II), [ 33 ] Fe (III), [ 19,34 ] and Cr (III) [ 35 ] have been reported in the past decade. Although these materials have exhibited remarkable performance for nitrogen separation, they still suffer from poor thermohydraulic stability or require external energy input for activation.…”
Section: Figurementioning
confidence: 99%
“…[1,[11][12][13] Polyamorphism in zeolites involves a low-density amorphous phase, which defines the onset of the structural collapse, and a high-density amorphous phase that forms later on further heating. [16] The thermal behavior of ETS-4 has been studied profoundly, [16][17][18][19] and although the material has been known since the late 1980s, [3] nothing unusual about its amorphous state is reported. [14] As a prominent member of that family, ETS-4 is a microporous titanosilicate that is known for its anticancer properties [15] and size-adjustable pores for gas separation.…”
Section: Stanislav Ferdov*mentioning
confidence: 99%
“…[2] Similar to zeolites, transition-metal silicates show porous-network topologies, but instead of consisting of AlO 4 tetrahedra, the building blocks of the SiO 4 units are combined with MO x polyhedra of various elements. [16] The thermal behavior of ETS-4 has been studied profoundly, [16][17][18][19] and although the material has been known since the late 1980s, [3] nothing unusual about its amorphous state is reported. [16] The thermal behavior of ETS-4 has been studied profoundly, [16][17][18][19] and although the material has been known since the late 1980s, [3] nothing unusual about its amorphous state is reported.…”
mentioning
confidence: 99%
“…Similar to zeolites, transition‐metal silicates show porous‐network topologies, but instead of consisting of AlO 4 tetrahedra, the building blocks of the SiO 4 units are combined with MO x polyhedra of various elements 14. As a prominent member of that family, ETS‐4 is a microporous titanosilicate that is known for its anticancer properties15 and size‐adjustable pores for gas separation 16. The thermal behavior of ETS‐4 has been studied profoundly,1619 and although the material has been known since the late 1980s,3 nothing unusual about its amorphous state is reported.…”
mentioning
confidence: 99%